Dynamics of markers of bone resorption in oral fluid in patients with generalized parodontitis during treatment - Fastovets, O. O.; Pavlov, S. V.; Lukash, A. Yu.; Павлов, Сергій Васильович (publishing center of the ESCBM, The Czech Republic, 2018)
The topicality of this study is due to the considerable prevalence of periodontal diseases, which is 20-50% of the total world population[1]. It is known that the most indicative of the inflammatory-destructive process in the periodontal tissues is an X-ray examination, there sults of which can be demonstrated to stabilize the pathological process as a result of treatment. However, to conclude about the state of alveolar bone is only possible in six months after treatment, which makes it impossible to monitor in its process for the purpose of correction. In this regard, the necessary task is the search for new non-invasive and informative methods of diagnosis, which may include biochemical examination of oral fluid[2].
Keywords: тези доповідей; generalized periodontitis; matrix metalloproteinase-8; oral fluid; diagnosis